George B. Simmons. The indian investment in family planning : an occasional paper of the population council. New Haven, Connecticut : The Van Dyck Printing Company, 1971. 213 p. - García, Brígida (Estudios Demográficos y Urbanos, 1971)
George B. Simmons, The Indian Investment in Family Planning : an Occasional Paper of the Population Council. New Haven, Connecticut, The Van Dyck Printing Company, 1971.